2019
DOI: 10.3892/ijmm.2019.4058
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles of isoastilbin against Alzheimer's disease via Nrf2‑mediated antioxidation and anti‑apoptosis

Abstract: By analyzing the L-glutamic acid (L-Glu)-induced apoptosis of PC12 cells and an AlCl3 combined with D-galactose (D-gal)-developed Alzheimer's disease (AD) mouse model, the protective effects of isoastilbin (IAB) against AD were systematically investigated in the present study. Pre-incubation with IAB for 3 h prior to treatment with 25 mM L-Glu decreased cell viability and inhibited apoptosis, suppressed the accumulation of intracellular reactive oxygen species, and restored mitochondrial membrane potential in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…It is a pro-apoptotic cytokines that combines with the apoptotic protease activating factor 1 (Apaf-1), sequentially recruits caspase-9. An executioner caspase-3 in mitochondria-mediated apoptosis is activated by activation of caspase-9 in glutamate-treated HT22 cells [32]. In the present study, in the presence of glutamate, the expressions of cytochrome c and cleaved caspase-9, -3 increased, but these expressions were significantly attenuated when HT22 cells were treated with 4,6 -anhydrooxysporidinone.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…It is a pro-apoptotic cytokines that combines with the apoptotic protease activating factor 1 (Apaf-1), sequentially recruits caspase-9. An executioner caspase-3 in mitochondria-mediated apoptosis is activated by activation of caspase-9 in glutamate-treated HT22 cells [32]. In the present study, in the presence of glutamate, the expressions of cytochrome c and cleaved caspase-9, -3 increased, but these expressions were significantly attenuated when HT22 cells were treated with 4,6 -anhydrooxysporidinone.…”
Section: Discussionsupporting
confidence: 41%
“…The transcription factor Nrf2 and activated HO-1 through Nrf2 transactivation enhance activities of antioxidant enzyme such as SOD and CAT, resulting in the enhancement of cellular antioxidant function, and inhibits the depolarization of mitochondrial membrane [ 32 ]. In the present study, in the presence of glutamate, the Nrf2 and HO-1 decreased, but these reductions were significantly enhanced when HT22 cells were co-treated with 4,6′-anhydrooxysporidinone, which may be involved in the protective effect of 4,6′-anhydrooxysporidinone against toxicity in glutamate-treated HT22 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5 a shows the significantly enriched terms ( q < 0.05) in biological process (BP) and molecular function (MF) categories. Obviously, most of the biological processes are related with AD, such as the negative regulation of inflammatory response (BP, GO:0050728) [ 48 ] and oxidation reduction process (BP, GO:0055114) [ 49 ]. Previous literature has revealed that anti-inflammatory drugs could significantly reduce the incidence of AD [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has revealed that anti-inflammatory drugs could significantly reduce the incidence of AD [ 48 ]. Moreover, accumulating evidence demonstrates that anti-oxidations are potentially promising strategies for safe and efficient treatment of AD [ 49 ]. Similarly, it is worthy to note that a great number of targets are associated with a variety of MF terms, which plays a role in the pathogenesis of AD.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription factor, Nrf2, has been found to play a critical role in neurological disorders like Alzheimer's disease (Fao, Mota, & Rego, 2019). Interestingly, several studies have evidenced that Nrf2 activation is involved in neuroprotective functions against a variety of neurotoxic agents (Su et al, 2016; Yu, Yuan, Chu, Wang, & Bi, 2019). Interestingly, Nrf2 activation has also been reported to provide protection against sevoflurane‐induced neurotoxicity, both in vitro and in vivo (Huang, Huang, & Ning, 2017; Tian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%